Student's self-concept, learning attitudes and perceptions of parenting style as correlates of academic achievement among Taiwanese adolescent girls - Hsiao, Meng-Pin (Animo Repository, 1991)
This study examines the relationship between academic achievement and perceived style, student's self-concept and learning attitudes. Academic Achievement measured by GPA was determined, Parenting Style Test, Tennessee Self-Concept Scale, and Learning Attitudes Test were administered to 120 sophomore students at Sacred Heart Girl's High School Taipei in the school year 1990-91. This is a descriptive study which made use of the survey method in gathering data. For statistical treatment, the Pearson Product Moment and stepwise multiple regression analysis were employed. The main findings of the study are the following: 1. There is a significant relationship between academic achievement and two specific parenting style of expectation (r=.289, p.01) and inconsistency (r2. There is a significant relationship between academic achievement and the student's self-concept in the area of self-behavior (r=.194, p.05), which means that the students who have higher scores on self-behavior in their self-concept tend to have better academic performance. 3. There is a significant relationship between academic achievement and overall learning attitudes (r=.270, p.01) and four subscales, namely learning method (r. 4. There is a significant relationship between parenting style perceived by students and their self-concept (r=.181, p.05) and their self-concept, and their overall learning attitudes (r5. Learning desire is the most predictive of academic achievement, followed by parenting styles of expectation, strictness, and inconsistency. The multiple R is .505 and MR squared is .255, which means that 25.5 percent of the Sacred Heart students' academic achievement is because of learning desire, expectation, strictness, and inconsistency. The researcher recommends that programs be designed to improve the learning desire and relations with parents to enhance student's academic achievement. More significantly, educational goals should be directed not only to academic, but to the development of the whole person.